2006
DOI: 10.1002/hep.21444
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic stimulates sinusoidal endothelial cell capillarization and vessel remodeling in mouse liver

Abstract: Trivalent arsenic [As(III)] is a well-known environmental toxicant that causes a wide range of organ-specific diseases and cancers. In the human liver, As(III) promotes vascular remodeling, portal fibrosis, and hypertension, but the pathogenesis of these As(III)-induced vascular changes is unknown. To investigate the hypothesis that As(III) targets the hepatic endothelium to initiate pathogenic change, mice were exposed to 0 or 250 parts per billion (ppb) of As(III) in their drinking water for 5 weeks. Arsenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
82
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(93 citation statements)
references
References 49 publications
(74 reference statements)
10
82
1
Order By: Relevance
“…Recently, Straub and colleagues 28 showed that prolonged exposure of mice to arsenic (III) initiated vascular remodeling by SEC capillarization, which was paralleled by increased sinusoidal CD31 expression, similar to our observation in HCC. 28 In this respect, our previous observation of increased numbers of alpha-smooth muscle actin-positive cells adjacent to CD34 expressing sinusoidal cells in HCC, 11 along with our current finding of increased Ang-1 in HCC, support the concept of sinusoidal remodeling in which recruitment of pericytes is stimulated by Ang-1. 29 Additionally, some tumors acquire their vasculature by vessel cooption instead of angiogenic sprouting.…”
Section: Discussionsupporting
confidence: 89%
“…Recently, Straub and colleagues 28 showed that prolonged exposure of mice to arsenic (III) initiated vascular remodeling by SEC capillarization, which was paralleled by increased sinusoidal CD31 expression, similar to our observation in HCC. 28 In this respect, our previous observation of increased numbers of alpha-smooth muscle actin-positive cells adjacent to CD34 expressing sinusoidal cells in HCC, 11 along with our current finding of increased Ang-1 in HCC, support the concept of sinusoidal remodeling in which recruitment of pericytes is stimulated by Ang-1. 29 Additionally, some tumors acquire their vasculature by vessel cooption instead of angiogenic sprouting.…”
Section: Discussionsupporting
confidence: 89%
“…4). It is well known that liver sinusoidal endothelial cells constitute unique sinusoid capillaries that differ from other capillaries in the body (Braet and Wisse, 2002;Lee et al, 2007;Straub et al, 2007), and are necessary for liver morphogenesis, even before the formation of vasculature (Matsumoto et al, 2001). The current study not only revealed predominant existence of CagApo-14 in the endothelial cells (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…Besides reducing the number of vessels, As 2 O 3 also influences the vascular morphology and function. Adding As 2 O 3 into the drinking water for mice induced significant vascular remodeling, with increased sinusoidal endothelial cell capillarization, resulting in decreased permeability and transport function (41). In another study, As 2 O 3 (10 mg/kg i.p.)…”
Section: Discussionmentioning
confidence: 99%